2013
DOI: 10.1159/000354601
|View full text |Cite
|
Sign up to set email alerts
|

Fodipir and Its Dephosphorylated Derivative Dipyridoxyl Ethyldiamine Are Involved in Mangafodipir-Mediated Cytoprotection against 7β-Hydroxycholesterol-Induced Cell Death

Abstract: Objective: Mangafodipir exerts pharmacological effects, including vascular relaxation and protection against oxidative stress and cell death induced by oxysterols. Additionally, mangafodipir has been proposed for cardiovascular imaging. The primary metabolites of mangafodipir, manganese dipyridoxyl ethyldiamine (MnPLED) and its constituent dipyridoxyl diphosphate (Dp-dp) also known as fodipir, are pharmacologically active. However, whether they affect oxysterol-induced cytotoxicity is currently unknown. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The effects of oxysteroids on structure and function of lysosomes have been proposed in a previous study (Boya, 2012). Excessive accumulation of oxysteroids in cells can lead to leakage of lysosomal membrane (Laskar et al, 2013; Yuan et al, 2016). However, as one of the important oxidation products of cholesterol, how 27-OHC influences the structure and function of lysosomes remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of oxysteroids on structure and function of lysosomes have been proposed in a previous study (Boya, 2012). Excessive accumulation of oxysteroids in cells can lead to leakage of lysosomal membrane (Laskar et al, 2013; Yuan et al, 2016). However, as one of the important oxidation products of cholesterol, how 27-OHC influences the structure and function of lysosomes remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol oxidation metabolites have been found to be one of the important factors inducing LMP (Boya, 2012). Cell experiments in vitro found that 7β-hydroxycholesterol (7β-OHC)and 7-ketocholesterol (7-KC) can induce cell death through LMP (Laskar et al, 2013; Yuan et al, 2016). However, whether 27-OHC, as one of the important oxysterols, can lead to LMP is still unclear.…”
Section: Introductionmentioning
confidence: 99%